2015
DOI: 10.1302/2046-3758.46.2000311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ibandronate on bending strength and toughness of rodent cortical bone

Abstract: ObjectivesThere remains conflicting evidence regarding cortical bone strength following bisphosphonate therapy. As part of a study to assess the effects of bisphosphonate treatment on the healing of rat tibial fractures, the mechanical properties and radiological density of the uninjured contralateral tibia was assessed.MethodsSkeletally mature aged rats were used. A total of 14 rats received 1µg/kg ibandronate (iban) daily and 17 rats received 1 ml 0.9% sodium chloride (control) daily. Stress at failure and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Our present findings are similar to the work of Blouin et al who described how at 1 month after an orchietomy, the architecture of cortical bone in aged male Wistar rats had not changed [42]. Vandenput et al showed a considerable difference in the volume of cortical bone 4 months after orchiectomy in aged male Wistar Hannover rats [45]. Another study also revealed that long term (> 4 months) after orchiectomy, the cortical bone mass was significantly affected [46].…”
Section: Discussionsupporting
confidence: 91%
“…Our present findings are similar to the work of Blouin et al who described how at 1 month after an orchietomy, the architecture of cortical bone in aged male Wistar rats had not changed [42]. Vandenput et al showed a considerable difference in the volume of cortical bone 4 months after orchiectomy in aged male Wistar Hannover rats [45]. Another study also revealed that long term (> 4 months) after orchiectomy, the cortical bone mass was significantly affected [46].…”
Section: Discussionsupporting
confidence: 91%
“…Mechanical and material properties of healthy and metastatically involved bone have also been assessed for treatments such as bisphosphonates [122][123][124][125][126][127], chemotherapeutics [128][129][130][131], photodynamic therapy (PDT) [85,132], Rank-L inhibitors [133][134][135][136], and multimodal treatment combinations [137,138]. Bisphosphonates and Rank-L inhibitors slow down bone turnover, leading to increased bone mineralization and slower osteolytic tumour growth.…”
Section: Treatment Effectsmentioning
confidence: 99%